Hubungan Karakteristik dan Pengetahuan Orang Tua tentang Cara Pemeliharaan Kesehatan Gigi dengan Kejadian Lubang Gigi pada Balita di Posyandu Jeruk Kelurahan Pondok Labu Jakarta Selatan - Ngatemi Ngatemi; Nur Afni (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
Child's Dental and Oral Health in Indonesia is still very alarming so it needs serious attention from health workers. The main problem that occurs in the oral cavity is dental caries. PDGI (Indonesian Dentist Association) states that at least 89% of caries sufferers are children. Based on the results of the characteristics of the health survey, the prevalence of dental caries in 3-5 year olds is 81.7%. This study aims to determine the relationship between the characteristics and knowledge of mothers about dental hygiene procedures with the incidence of tooth holes in infants in Posyandu Jeruk, Pondok Labu Village, South Jakarta in 2018. This study was a descriptive study with a cross sectional design. The research sample used total sampling totaling 47 mothers of children aged 4-5 years who came to the Posyandu Jeruk. Data collection through questionnaires and observation of tooth holes by officers. Data analysis was conducted in univariate, bivariate, and multivariate. The results of univariate analysis showed that the incidence of tooth decay was mostly in the high category (57.4%), mother age <32 years (66.6%), high maternal education (66.0%), and knowledge was mostly high (63.8 %). The results of the bivariate analysis, the variables that were significantly related to the incidence of tooth holes were education (p = 0.007 and OR = 9,692), and knowledge (p = 0.004 and OR = 11,250). Whereas the non-mean is age (p = 0.667). The results of multivariate analysis, the dominant variable associated with the incidence of tooth holes in infants is maternal knowledge (OR = 9,068).